2007
DOI: 10.1016/j.bbapap.2007.01.002
|View full text |Cite
|
Sign up to set email alerts
|

ANS fluorescence: Potential to augment the identification of the external binding sites of proteins

Abstract: Abstract8-anilino-1-naphthalenesulfonic acid (ANS) is believed to strongly bind cationic groups of proteins and polyamino acids through ion pair formation. A paucity of data exists on the fluorescent properties of ANS in these interactions. ANS binding to arginine and lysine derivatives was studied by fluorescence and circular dichroism spectroscopies to augment published information attained by isothermal titration calorimetry (ITC).Fluorescence enhancement with a hypsochromic shift results from the interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
241
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 348 publications
(247 citation statements)
references
References 18 publications
5
241
0
1
Order By: Relevance
“…Fluorescence enhancement upon binding to proteins can result from ion pairing interactions, hydrophobic interactions, restricted mobility or any combination of these factors [33][34][35][36]. EPR spectra of spin labeled G-strand mutants complexed with ANS in molten globule state are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescence enhancement upon binding to proteins can result from ion pairing interactions, hydrophobic interactions, restricted mobility or any combination of these factors [33][34][35][36]. EPR spectra of spin labeled G-strand mutants complexed with ANS in molten globule state are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Both the binding and fluorescence properties of ANS are influenced strongly by local environmental variables, which include not only hydrophobicity but also neighboring charged groups and the solvent polarity and viscosity (43,44,83). Interaction of positively charged arginine or lysine side chains with the sulfonate group of ANS (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…ANS is a small amphipathic dye (Fig. 1B) that has been used as a sensitive probe to detect hydrophobic pockets on protein surfaces (41)(42)(43)(44). Free ANS exhibits only weak fluorescence that is maximal near 520 nm, but when ANS binds to a hydrophobic site in a partially or fully folded protein, the fluorescence peak increases in amplitude and shifts to a shorter wavelength (42).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it has been shown that the electrostatic interaction alone is not sufficient to provide high binding affinity for ANS (K d < 1 mM) (44). For internal ANS binding, in addition to the electrostatic interaction, hydrophobic and van der Waals interaction should be considered.…”
Section: Binding Experiments With Ans 1npn and Tns: Electrostatic Cmentioning
confidence: 99%